A Scalable and Reliable OSS/BSS for User Migration in IMS - Sven Pärand; Andres Kirikal (International Journal of Applied Methods in Electronics and Computers, 2015)
Telecommunications operators moving away from legacy networks towards next generation networks (NGN) are faced with the complex task of migrating not only users and services but modifying or designing and rebuilding supporting systems as well. New service delivery platforms (SDP) like IP multimedia subsystem (IMS) are fundamentally different compared to the old ones and require a novel approach from both the business and technology point of view. The main emphasis in the latter case is namely on operations support systems/business support systems (OSS/BSS) and the way these have to change in conjunction with the development of SDPs. The current paper addresses just this matter and is focused mainly on technical aspects and more specifically user migration. Different migration cases have been brought forth, clearly defining their differences while keeping in mind the issues of reliability and scalability since migration towards NGN for most operators will happen with great volumes. The migration process and its relation to supporting systems has been expanded upon to specify how and what has changed during the path towards NGN, especially with regards to users. Also a novel system for provisioning and migration has been discussed to illustrate a possible way for large scale user migration.